Pengaruh Brand Image Scarlett Whitening dan Brand Ambassador EXO terhadap Loyalitas Konsumen dengan Kepuasan sebagai Variabel Mediasi pada Generasi Z di Indonesia - Keany Revinsky Silaen; Fransius Awaldo Damanik (Jurnal Minfo Polgan, 2026)
This study aims to analyze how Scarlett Whitening's brand image and EXO's brand ambassador influence consumer loyalty and satisfaction as mediating variables among Generation Z in Indonesia. This study used a purposive sampling technique and involved respondents from this group who were familiar with Scarlett Whitening, EXO as a brand ambassador, and had purchased or used Scarlett Whitening products. Primary data was collected using Google Forms with a Likert scale, using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method through SmartPLS 4. The results showed that Brand Ambassador had a positive and significant effect on satisfaction of 0.519 and consumer loyalty of 0.279. In addition, brand image had a positive and significant effect on satisfaction of 0.329 and consumer loyalty of 0.294. Furthermore, consumer loyalty had a positive and significant effect on satisfaction of 0.291. The results of the mediation test indicate that satisfaction mediates the influence of Brand Ambassador on consumer loyalty with an indirect effect value of 0.151 and the influence of Brand Image on consumer loyalty with an indirect effect value of 0.096. These findings indicate that Generation Z has several factors that influence consumer loyalty to Scarlett Whitening, namely brand image and the attractiveness of the brand ambassador, as well as consumer satisfaction after using the product.